Analisis Pengaruh Jumlah Uang Beredar, Suku Bunga, dan Nilai Tukar terhadap Tingkat Inflasi di Indonesia Periode Tahun 2001-2020 - Dzaky Abghian Taufik (Universitas Diponegoro, 2021)
The Corona virus or COVID-19 pandemic has a huge impact on the world economy. The Indonesian government has taken a comprehensive policy in the fiscal and monetary fields to deal with the Covid-19 pandemic. This study aims to analyze the long-term and short-term effect of the Money Supply (JUB), Interest Rate (SB), and Exchange Rate (NT) on the Inflation Rate (INF) partially or simultaneously on the Inflation Rate (INF) in Indonesia in the period 2001 to 2020. The research method used is a time series econometric model, using the ECM (Error Correction Model) method. The data used are semiannual quantitative data in the period 2001-2020. Secondary data obtained from the results of publications conducted by Bank Indonesia (BI) and Badan Pusat Statistik (BPS) in the form of processed data published. The results showed that the money supply partially had a positive and significant effect in the long term, while in the short term it had a partially positive and insignificant effect on the inflation rate. Interest rates partially had a negative and significant effect both in the short and long term on the inflation rate. Exchange Rate partially has a positive and insignificant effect in the long and short term on the Inflation Rate. The Money Supply, Interest Rates, and Exchange Rates simultaneously and significantly affect the Inflation Rate in the long term and short term in Indonesia in the period 2001 to 2020.